Can We Make a Difference? Prejudice Towards Asylum Seekers in Australia and the Effectiveness of Antiprejudice Interventions. (June 2015) - Pedersen, Anne; Hartley, Lisa K.
Over the past few decades, Australia has implemented increasingly restrictive measures to try and deter the arrival of asylum seekers. In our article, we review what is known in the literature about the antecedents of prejudice against asylum seekers. We outline 11 mechanisms, or variables, as being particularly important. We then draw out the practical implications as they relate to antiprejudice interventions. Within the research and implications, we discuss our own experiences of working directly with asylum seekers over the past decade and in running antiprejudice interventions. We conclude that even though the situation is bleak in Australia at the time of writing this article (at the end of 2014), we must continue with attempts to combat the demonisation of asylum seekers both on an individual level and a structural level.